Podemos : una historia colectiva - Guedán Menéndez, Manuel (Tres Cantos, Madrid, España : Akal, 2016)
An oral history of the Spanish political party Podemos.
Includes bibliographical references.
Online resource; title from ePub title page (Digitalia, viewed July 27, 2019)
Keywords: Podemos (Political party) -- History; Political parties -- Spain; Social movements -- Spain -- History -- 21st century; Spain -- Politics and government -- 21st century; Electronic books